High throughput discovery of novel polymers to prevent biofilm formation on blood-contacting medical devices - Singh, Taranjit (2017)
Biofilm formation on blood-contacting medical devices is a major healthcare problem causing significant morbidity, mortality and economic burden on healthcare systems around the world. In this thesis, a high throughput material microarray approach was used to screen a library of novel acrylate and methacrylate based polymer materials for bacterial attachment, haemostasis and immune system interactions. Polymer microarray printing was first optimised to produce confined spots of each material, confirmed by ToF-SIMS. The polymer microarray was incubated in human blood and analysed for blood proteins, cells and immune component attachment on each spot of the microarray. The blood exposed microarray was then incubated in RPMI-1640 media containing Pseudomonas aeruginosa and Staphylococcus aureus in two separate experiments to model a bacterial challenge on blood-contacting devices. These high throughput screening experiments identified nine haemocompatible bacterial resistant ‘hit’ materials for further analysis.